PENERAPAN HIGIENE DAN SANITASI PENGELOLAAN MAKANAN UNTUK MENJAMIN KEAMANAN PANGAN DI KANTIN PUJA SERA UNIVERSITAS ANDALAS - Fea Firdani; Defriman Djafri; Azyyati Ridha Alfian; Aulia Rahman (LPPM Universitas Andalas, 2020)
The implementation of management hygiene and sanitation at the DPR's Puja Sera Canteen (Under a Shady Tree) is very important because it is a canteen with high activity in Andalas University. Based on the results of the survey on 6 February 2020, it was found that condition of the DPR Puja Sera Canteen (Under a Shady Tree) still needed implementation of hygiene and sanitation management to ensure the health of visitors or students. The solution offered is education on good food production methods for home industries (CPPB-IRT). The method used to realize the implementation of food handling hygiene and sanitation includes identification and inspection of hygiene and sanitation, assessment of examination results, providing education to food handlers who are not / not / inadequate. The results of examination became a reference for correcting deficiencies in the implementation of hygiene and sanitation at the DPR's Puja Sera Canteen (Under a Shady Tree) Unand to be equipped according to requirements of a healthy canteen so that the DPR Puja Sera Canteen (Under a Shady Tree) Unand could meet requirements to become a healthy canteen. The results of the examination for issuance of home industry food production certificates (SPP-IRT) of the 14 assessment criteria show that DPR's Puja Sera Canteen is at level III, found 1-4 serious problems that should be corrected to obtain SPP-PIRT certification. Serious problems include 1) buildings and facilities, 2) water supply and water supply facilities, 3) hygiene and sanitation facilities and activities, 4) employee health and hygiene.